To find the equation that is true when k = -12, we substitute -12 in place of k in each of the given equations and see which equation gives a true statement.
Let's substitute -12 in each equation:
A) 3k - 11 = 16
3(-12) - 11 = 16
-36 - 11 = 16
-47 = 16 (false)
B) -53 + 4k = 5
-53 + 4(-12) = 5
-53 - 48 = 5
-101 = 5 (false)
C) k + 17 = 13
-12 + 17 = 13
5 = 13 (false)
D) k/4 + 2.5 = 0.5
-12/4 + 2.5 = 0.5
-3 + 2.5 = 0.5
-0.5 = 0.5 (false)
None of the given equations are true when k = -12.
Which equation is true when k = –12?
Responses
3k – 11 = 163 k – 11 = 16
B –53 + 4k = 5–53 + 4 k = 5
C
k
3 + 17 = 13 k 3 + 17 = 13
D
k
4 + 2.5 = 0.5
1 answer